Percakapan antara Teologi Karl Barth dengan Nurcholis Madjid dan Ibnu Taymiyyah: Sebuah Diskursus tentang Keselamatan Universal dan Rahmat Ilahi - Saragih, Denni Boy (Indonesian Journal of Theology, 2024)
This study presents a pioneering dialogue between Karl Barth’s Christian theology and Islamic theological perspectives in the Indonesian context, focusing specifically on the concept of universal salvation. The primary interlocutors are Nurcholish Madjid, interpreting Ibn Taymiyya, and Karl Barth’s theology. Barth’s universalism envisions an inclusive future for humanity, elaborated in Barth’s exposition of the theme “Jesus is Victor,” suggesting a universal reprieve from divine eschatological judgment. Correspondingly, Madjid’s interpretation of Islamic theology proposes a universally hopeful future, recognizing the broad spectrum of divine revelation across various religious traditions, thereby fostering a sense of shared hope among diverse religious followers. Ibn Taymiyya, often misconceived as a figurehead for radical elements, is depicted in this essay as advocating a form of universalism where divine mercy ultimately triumphs over retribution. This article contends that this mutual anticipation of universal salvation can pave the way for meaningful Christian-Islamic interactions in the Indonesian milieu, contributing significantly to interfaith dialogue and understanding.